Human Bot Fly, torsalo (Central America), moyocuil (Mexico), berne (Brasil), mucha (Colombia, mirunta (Peru), and ura (Argentina, Paraguay, and Uruguay), Dermatobia hominis (Linnaeus, Jr.) (Insecta: Diptera: Oestridae) - Stephanie K. Larrick; C. Roxanne Rutledge-Connelly (EDIS)
EENY-440, a 6-page illustrated fact sheet by Stephanie Larrick and Roxanne Connelly, is part of the Featured Creatures Collection. It describes this large, densely haired fly native to Central and South America, which, in its larval stage, infests the skin of mammals causing painful pustules, a condition known as myiasis. Includes references. Published by the UF Department of Entomology and Nematology, September 2008.